Automated monitoring and control system for bottom clean raceway fish culture technology - Mobin, Md Faijul Islam; Wadood, A K M Nahid Bin; Islam, Fardin; Alam, Sheikh Mahfuz (Brac University, 2023)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.